A Multimodal Educational Boot Camp for Training Fellows in Pediatric Extracorporeal Membrane Oxygenation (ECMO) - Yujin Park; Gail Hocutt; Elizabeth Wetzel; Nathan Swinger; Kellie Pearson; Kamal Abulebda; Brian Gray (MedEdPORTAL)
Introduction Pediatric extracorporeal membrane oxygenation (ECMO) management presents unique challenges in acute care settings, requiring specialized expertise to manage critically ill children. Medical and surgical fellows often manage these patients, but prior residency training rarely provides sufficient ECMO exposure. We developed and evaluated a multimodal pediatric ECMO boot camp for new fellows. Methods This boot camp was implemented during 5-hour sessions in August 2021, August 2022, and August 2023. The curriculum included a 45-minute introductory didactics session, 30-minute hands-on circuit demonstration, and four 30-minute small-group activity stations. To assess knowledge acquisition, pre- and posttests were administered; participants also completed a post–boot camp survey to evaluate their confidence and provide feedback. Results Forty-nine participants completed the boot camp, including 18 critical care, four cardiology, 11 pediatric surgery, 12 cardiothoracic surgery, and four pediatric emergency medicine fellows. Pre- and posttests demonstrated significant improvement in knowledge of ECMO circuit components and pressures (56% vs. 76%, p < .001). All of our participants agreed or strongly agreed that participating in the boot camp increased their confidence in troubleshooting ECMO emergencies. The inclusion of fellows from various clinical disciplines, offering a rich diversity of perspectives, was particularly valued by participants. Discussion Our results demonstrate the feasibility and effectiveness of establishing a pediatric ECMO boot camp to train new surgical and medical fellows. The curriculum not only improved ECMO knowledge but also boosted learners’ confidence in managing ECMO-related challenges.